A Model for Regenerative Regional Development Based on Ecosystems, Community Participation, and Environmental Policy in Papua - Halomoan Hutajulu (Westscience Press, 2026)
This study develops and empirically tests a regenerative regional development model integrating ecosystem-based development, community participation, and environmental policy in Papua, Indonesia. Regenerative development extends beyond conventional sustainability by emphasizing ecosystem restoration, social inclusion, and institutional effectiveness within socio-ecological systems. Despite its growing conceptual relevance, empirical validation of integrated regenerative models in peripheral and ecologically sensitive regions remains limited. Using a quantitative explanatory design, primary data were collected from 110 stakeholders involved in regional development and environmental governance in Papua and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that environmental policy plays a central and dominant role in shaping regenerative regional development, demonstrating a strong and significant direct effect. Community participation and ecosystem-based development do not show significant direct effects on regenerative outcomes; however, both exert significant indirect effects through environmental policy. These findings confirm the mediating role of environmental policy as an institutional mechanism that translates ecological principles and participatory processes into measurable regenerative outcomes. The model explains 64.8% of the variance in regenerative regional development and demonstrates strong predictive relevance. The study contributes theoretically by operationalizing regenerative development into measurable constructs, methodologically by applying SEM-PLS to an integrated socio-ecological framework, and practically by providing evidence-based guidance for policymakers seeking inclusive and ecologically grounded development pathways in Papua and similar regions.